Cooperative Behavior in the Ultimatum Game and Prisoner’s Dilemma Depends on Players’ Contributions - Bland, Amy R.; Roiser, Jonathan P.; Mehta, Mitul A.; Schei, Thea; Sahakian, Barbara J.; Robbins, Trevor W.; Elliott, Rebecca (Frontiers in Psychology, 2017)
Economic games such as the Ultimatum Game (UG) and Prisoner’s Dilemma (PD) are widely used paradigms for studying fairness and cooperation. Monetary versions of these games involve two players splitting an arbitrary sum of money. In real life, however, people’s propensity to engage in cooperative behaviour depends on their effort and contribution; factors that are well known to affect perceptions of fairness. We therefore sought to explore the impact of relative monetary contributions by players in the UG and PD. Adapted computerised UG and PD games, in which relative contributions from each player were manipulated, were administered to 200 participants aged 18-50 years old (50% female). We found that players’ contribution had large effects on cooperative behaviour. Specifically, cooperation was greater amongst participants when their opponent had contributed more to joint earnings. This was manifested as higher acceptance rates and higher offers in the UG; and fewer defects in the PD compared to when the participant contributed more. Interestingly, equal contributions elicited the greatest sensitivity to fairness in the UG, and least frequent defection in the PD. Acceptance rates correlated positively with anxiety and sex differences were found in defection behaviour. This study highlights the feasibility of computerised games to assess cooperative behaviour and the importance of considering cooperation within the context of effortful contribution.